Radiation-Induced Partial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Intractable epilepsy in 3 patients treated with low-dose irradiation to "strawberry" scalp nevi in infancy is reported from the Montreal Neurological Institute and Hospital, Montreal, Quebec, Canada.